Electrical Pumping in Solid-State Lasers: Recent Advances (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article aims to provide a comprehensive review of recent advances in the field of electrical pumping in solid-state lasers. The transition from traditional optical pumping methods to electrical pumping has opened new avenues for efficiency, miniaturization, and application of solid-state lasers. The article will explore the fundamental principles of electrical pumping, its historical development, and the technological innovations that have facilitated this shift. Key breakthroughs in materials science, semiconductor technologies, and laser cavity designs will be highlighted. Additionally, the article will examine the practical implications of these advances in various industries, including telecommunications, medical diagnostics, and defense. By analyzing current research and emerging trends, the article will offer insights into the future directions of electrically pumped solid-state lasers and their potential to revolutionize laser technology.